Telaah Kritis Eksistensi Pesantren sebagai Refleksi Pendidikan Islam Holistik dalam Membentuk Generasi Muslim Berkarakter - Sufirmansyah; Lailatul Badriyah (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2020)
This article reveals the position of pesantren as a reflection of holistic Islamic education. Compared to other educational institutions, pesantren has a distinct advantage in terms of habituating Islamic values for students. Using a qualitative methodology and van Dijk's discourse analysis approach, this article was prepared by examining and analyzing all relevant references for the sake of obtaining a systematic conclusion. This article comes to the synthesis that pesantren has tremendous potential in shaping the personality of future generations of Muslims based on the Qur'an and Hadith. The role of the kiai is very vital and supported by activities laden with high levels of Islamic morality making pesantren have a very promising bargaining value for the realization of the objectives of Islamic education, namely the formation of our people. Therefore, without ignoring other Islamic educational institutions, pesantren must continue to be supported and at the same time synergize with other institutions in order to be able to spread these characteristics so that future generations of Muslims truly have Islamic character in their daily lives.